2011
DOI: 10.2528/pierm11052312
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Absorbing Characteristics of Asphalt Mixes With Carbonyl Iron Powder

Abstract: Abstract-Power microwave was adopted to heat asphalt mixes with carbonyl iron powder (CIP) by its microwave absorbing characteristics. The Arch reflectivity system was employed for reflectivity tests in the frequency range of 2.0 ∼ 4.0 GHz, and road properties of the asphalt mixes with different heating techniques were studied. The results indicate that 30 mm thickness of the asphalt mixes with the ratio of CIP absorber to asphalt 0.1 : 1.5, can effectively absorb microwave with a −19.1 dB absorbing peak at 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…5(a) shows part of spherical absorbers stacked in a flat box with size 200 mm à 200 mm à 80 mm, with dry sand filled in the space of absorbers to avoid absorbers moving during measurement. The absorbing effectiveness of stacked structure absorber is measured by arch reflectivity method [18]. Consider the dry sand could also absorb electromagnetic wave, the measure steps are slightly different from that of [18], i.e., the Pm in [18] is the reflected power of metal plane (ideal reflector), while in this paper it is the reflected power of metal plane with the flat box placed on it.…”
Section: Absorbing Effectiveness Bymentioning
confidence: 99%
See 1 more Smart Citation
“…5(a) shows part of spherical absorbers stacked in a flat box with size 200 mm à 200 mm à 80 mm, with dry sand filled in the space of absorbers to avoid absorbers moving during measurement. The absorbing effectiveness of stacked structure absorber is measured by arch reflectivity method [18]. Consider the dry sand could also absorb electromagnetic wave, the measure steps are slightly different from that of [18], i.e., the Pm in [18] is the reflected power of metal plane (ideal reflector), while in this paper it is the reflected power of metal plane with the flat box placed on it.…”
Section: Absorbing Effectiveness Bymentioning
confidence: 99%
“…The absorbing effectiveness of stacked structure absorber is measured by arch reflectivity method [18]. Consider the dry sand could also absorb electromagnetic wave, the measure steps are slightly different from that of [18], i.e., the Pm in [18] is the reflected power of metal plane (ideal reflector), while in this paper it is the reflected power of metal plane with the flat box placed on it. Therefore, the absorbing effectiveness of flat box with dry sand filled in are elimated.…”
Section: Absorbing Effectiveness Bymentioning
confidence: 99%
“…For example Wang et al (9,10) used carbonyl iron powder. Gallego et al (11) added a bituminous steel wool to the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Field applications in Montreal and Quebec proved that microwave radiation with a frequency of 2.45 GHz could be effectively coupled into bituminous pavements to a depth of 12 cm without overheating the top layer of the asphalt road. Such frequency is usual in asphalt pavement microwave maintenance vehicles and microwave radiation heaters (Wang et al, 2011). A patent of Osborne and Hutcheson (1987) registered the potential of a modified asphalt composite with dispersed granular material, to allow microwaves absorption, as feasible for reconditioning and asphalt repair.…”
Section: The Use Of Microwave Radiation For Asphalt Mixtures Heatingmentioning
confidence: 99%
“…On the other hand, several studies have demonstrated that micro-wave radiation may be applied for crack healing purposes (Bosisio, Spooner, & Granger, 1974;Osborne & Hutcheson, 1987;Sangadji & Schlangen, 2013;NorambuenaContreras, Serpell, Valdés Vidal, González, & Schlangen, 2016;Zanko et al, 2016) as well as on the production and recycling of asphaltic pavements (Bosisio, et al, 1974;Osborne & Hutcheson, 1987;Norambuena-Contreras et al, 2016;Wang, Zhao, Yang, & Wang, 2011). Microwave industrial devices have already been designed especially for this application (Eliot, 2013).…”
Section: Introductionmentioning
confidence: 99%